Reductant‐Free Synthesis of Silver Nanoparticles by Functionalized Hollow Doughnut Mesoporous Silica Nanoparticles for Preparation of Catalytic Nanoreactor. Issue 6 (12th February 2018) - Vo, Nhat Tri; Patra, Astam K.; Kim, Dukjoon
Abstract: This work reports a detailed investigation about functionalization of hollow doughnut mesoporous silica nanoparticles (hd‐MSN) by N 1 ‐(3‐Trimethoxysilylpropyl) diethylenetriamine (DAEAPTS). Interestingly, here we experimentally show that the tri‐amino functional groups on hd‐MSN (hd‐MSN‐NH2 ) act as capping agent as well as reducing agent for silver ions (Ag + ) and the reduction reaction process can significantly influence the structure of the silver nanocrystals. Thus, we have deposited uniform 4.2 nm silver nanocrystals on the hd‐MSN‐NH2 nanoparticles without any reducing agents. The size and the crystalline structure of Silver nanoparticles (Ag NPs) and silica nanoparticles were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM) and wide‐angle X‐ray diffraction, respectively. The mechanism of reduction of Ag + was clearly studied by FT‐IR, FT‐Raman, XRD and XPS studies. Ag/hd‐MSN‐NH2 with special shape (hollow doughnut shape) could incorporate Ag NPs both inside and outside of hd‐MSN. Here Ag/hd‐MSN‐NH2 worked as nanoreactor. In our condition for catalytic reduction of 4‐nitrophenol, the reaction rate reached 4.1 x10 −3 s −1 which is higher than many previous results. The Ag/hd‐MSN‐NH2 nanocatalyst shows excellent reusability and high efficiency even after 10 cycles. Abstract : A new method for preparation of silver nanoparticles (Ag NPs) doped N 1 ‐(3‐Trimethoxysilylpropyl) diethylenetriamine (DAEAPTS) functionalization hollow doughnut mesoporous silica (hd‐MSN) is developed. The tri‐amino functional groups on hd‐MSN (hd‐MSN‐NH2 ) act as capping agent as well as reducing agent for silver ions, and the reduction reaction process can significantly influence the structure of the silver nanocrystals. The Ag/hd‐MSN‐NH2 nanoreactor shows excellent reusability and high efficiency even after 10 cycles.